Karakter Disiplin dan Karakter Religius: Pengaruhnya terhadap Kemampuan Numerik Peserta didik - Pradana, Kenny Candra; Fatimah, Okis; Rahmawati, Yasinta; Windya, Pelangi Mutia; Erprabowo, Alfian (Edumatica : Jurnal Pendidikan Matematika, 2023)
Numerical abilities and educational character are very important in learning mathematics at school, some of the student characters that must be considered are disciplinary and religious characters. This study aims to determine the effect of students' disciplinary and religious character on numerical ability. This study uses survey research methods with descriptive research types with survey techniques. The population used in this research is all SMP/MTs/equivalent in North Lampung for the 2020/2021 academic year. The sampling technique used in this study was the cluster random sampling technique, so that MTs Negeri 1 North Lampung and MTs Negeri 2 North Lampung were obtained as samples. Three classes were taken from each school as a sample consisting of representatives from class VII, VIII and IX. The instruments used in this study were a numerical ability test and a disciplinary character questionnaire and a religious character. Data analysis technique using Multiple Linear Regression analysis. Based on the results of the analysis, it was found that the influence of the disciplinary character of the religious character on students' numerical abilities was very strong, amounting to 73.6 percent. The results of the regression equation analysis show Y = 32.586 + 0.286X1 + 0.368X2. This equation shows that every 1 increase in the disciplinary character variable will affect the numerical ability variable by 0.286. Likewise, for the coefficient of the religious character variable, it will affect the numerical ability variable of 32.586.